Mushaf Al-Qur’an dengan Iluminasi Bunga Matahari di Museum Sejarah Al-Qur’an Sumatera Utara - Muhamad Halim, Rabia’tul A’dawiyah Binti; Hery Sahputra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Qur'an is a precious book and also something historic for all followers of Islam. Indonesia is the largest Muslim country in the world and it turns out that in Indonesia there are many historical mushafs left over from the Kingdom, Islamic boarding schools or mosques in Indonesia.In Indonesia, there are many Islamic educational institutions that teach the Qur'an. However, the students of Qur'anic science do not have wide access to the study of ancient mushaf, they do not know how to apply their knowledge to the corpus of mushaf. In addition, ancient relics are very valuable assets in order to reveal the history of the past. Because Indonesia is one of the nations that has a diverse civilization. The heritage of its religious population is scattered in various regions in Indonesia. The problem that arises here is that most of the Indonesian population still does not know the types of Al-Qur'an and how its history. Each Al-Qur'an in Indonesia has its own specialty such as the decoration (illumination) displayed in each region. This Muslim guidance object also contains interesting philosophies. Therefore, the Al-Qur'an needs to be museumized with the aim of being cared for, maintained and exhibiting the beauty of the Al-Qur'an to the entire community. Because the Qur'an is exhibited, it must have something to do with Islam. Therefore, Mushaf Al-Qur'an with Iluminasi Bunga Matahari is one of the ancient Al-Qur'an in the Al-Qur'an History Museum of North Sumatra